2016
DOI: 10.1088/0964-1726/25/8/084009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of microcapsule—catalyst particles healing system in high performance fibre reinforced polymer composite

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms Assessment of microcapsule -catalyst particles healing system in high performance fibre reinforced polymer composite. AbstractAutonomous self-healing in carbon fibre reinforced polymer (CFRP) is demonstrated using epoxy resin filled microcapsules and a solid-state catalyst. Microcaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…To the best of the authors’ knowledge, very few single or double capsule systems have been demonstrated in FRPs that meet the selection criteria specified. One exception published by Bolimowski et al utilizes the same chemistry as Coope et al to functionalize unidirectional (UD) composite specimens. Although Bolimowski et al did not report fiber volume fraction, it can be inferred from the cure procedure reported, and the manufacturer's data, that the sample fiber volume should be between 52% and 56%.…”
Section: Self‐healing Fiber‐reinforced Polymer Composites: the State mentioning
confidence: 99%
See 4 more Smart Citations
“…To the best of the authors’ knowledge, very few single or double capsule systems have been demonstrated in FRPs that meet the selection criteria specified. One exception published by Bolimowski et al utilizes the same chemistry as Coope et al to functionalize unidirectional (UD) composite specimens. Although Bolimowski et al did not report fiber volume fraction, it can be inferred from the cure procedure reported, and the manufacturer's data, that the sample fiber volume should be between 52% and 56%.…”
Section: Self‐healing Fiber‐reinforced Polymer Composites: the State mentioning
confidence: 99%
“…One exception published by Bolimowski et al utilizes the same chemistry as Coope et al to functionalize unidirectional (UD) composite specimens. Although Bolimowski et al did not report fiber volume fraction, it can be inferred from the cure procedure reported, and the manufacturer's data, that the sample fiber volume should be between 52% and 56%. Double‐cantilever beam (DCB) specimens demonstrated a maximum healing efficiency of 44% with a catalyst loading of 10 wt%; however, even this modest recovery is amplified by the significant detrimental effect the inclusion of the microcapsules and catalyst particles has on initial fracture toughness: the strain energy release rate of the virgin‐functionalized specimens only averaged 22% of that of the nonfunctionalized control specimens.…”
Section: Self‐healing Fiber‐reinforced Polymer Composites: the State mentioning
confidence: 99%
See 3 more Smart Citations